Mechanization adds value to cassava products - Sajeev, M. S.; Sheriff, J. T. (Indian Horticulture, 2019)
Various starch extraction machineries having different capacities are well suited for both micro and small-scale ventures. Chipping machines are simple to operate with low energy and cost input to produce quality flours. Harvesters mainly reduce the drudgery involved in uprooting cassava tubers by reducing the effort of lifting tubers to one-fourth of that of manual methods. Other machineries also help utilize starch and flour in a more effective way in feed and industrial sectors.